What Every Psychologist Should Know About the P-Value: What it Means and What it Doesn`T Mean - A Heuristic Approach - Giacomuzzi, Salvatore; Kocharian, Alexander; Barinova, Natalia (Psychological Counseling and Psychotherapy, 2021)
Synopsis: The topic in this paper has been the subject of an intense controversy over the past years. The following remarks are aimed at providing a simplified introduction to the psychological concepts of significance. A mathematical presentation is intentionally avoided because, on the one hand, the readership decreases exponentially with each mathematical formula and, on the other hand, these are given in detail in the special lectures or in scientific presentations. Starting from the historical background, the focus here is on the concepts of the ideas on the one hand, and on the other hand, the modern discussion of these concepts will be presented briefly.